ANALISIS PENGARUH, SELF-ESTEEM, KECEMASAN, ATTACHMENT, TERHADAP FENOMENA PILIH KASIH DI SEKOLAH DASAR - nur elisa vyrna; Riska Aulia; Aisyach Nurul Syahputri; A. Muhajir Nasir (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the influence of self-esteem, anxiety, and attachment on the emergence of favoritism within teacher–student interactions in elementary schools. Using a descriptive qualitative approach, the research was conducted at MI Muhammadiyah 11 Bara-Barayya Makassar, involving several students through observations, semi-structured interviews, and documentation. The findings show that favoritism is primarily triggered by differences in academic ability and social closeness between teachers and students, such as familial relationships or neighborhood proximity. These conditions contribute to decreased student self-esteem, increased academic anxiety, and weakened emotional attachment to the teacher. The phenomenon also affects students’ learning motivation, classroom social dynamics, and participation in learning activities. The study concludes that although unintentional, unequal treatment in the classroom generates perceptions of unfairness that significantly impact students’ psychological and social conditions. Therefore, teachers are encouraged to implement inclusive classroom management and provide equitable reinforcement and attention to all students